THE QUR'AN AND SOCIAL SOLIDARITY: ANALYSIS OF CONTEMPORARY APPLICATIONS IN INDONESIAN URBAN SOCIETY - Ariyadi, Samsul (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the concept of social solidarity and religious values, especially those contained in the Qur'an. Social solidarity has long been the focus of discussion in various disciplines, ranging from sociology, political science, to Islamic studies. In the midst of the increasingly complex dynamics of urbanization in Indonesia, the question of how religious values, especially those contained in the Qur'an, can encourage collective action based on social justice is very relevant. By examining in depth the relationship between the teachings of the Qur'an and social solidarity, this article contributes to the development of social theory and practice in urban Indonesian society. It is hoped that the findings and recommendations presented can be a reference for academics, researchers, and policymakers in formulating strategies for integrating Islamic values into contemporary social dynamics, so that in the end it can produce a more just, inclusive, and dignified society. The results of the study show that there is a strong integration between the theological message in the Qur'an and the dynamics of social interaction, as well as its implications in the formation of pro-people public policy. Thus, the conceptual framework proposed in this study not only makes a theoretical contribution to the development of Islamic studies and sociology, but also offers practical recommendations that are applicable to the strengthening of social solidarity in the modern era. This study suggests that further studies can explore more empirical aspects, involving field data and participatory analysis, to ensure that the values of the Qur'an are truly integrated into social life and public policy as a whole. This research invites further dialogue between stakeholders in an effort to realize solid social solidarity, as a tangible manifestation of the application of the principles of goodness and justice enshrined in the Qur'an.